Obliterative lower airway lesions in childhood: Bronchoscopic diagnosis and clinical spectrum. Issue 3 (4th March 2013) - Quizon, Annabelle; Minic, Pedrag; Pohunek, Petr; Tal, Asher; Colin, Andrew A.
Abstract Previous reports have described structural airway abnormalities in children with non‐cystic fibrosis chronic supportive lung disease as well as obliterative membranes in the major bronchi of cystic fibrosis patients. The putative paradigm proposed in the evolution of these membranes invokes intense inflammation resulting in granulation tissue and neovascularization with the formation of pyogenic granuloma and eventually fibrosis. Our series of four cases widens the spectrum of conditions that may be conducive to large airway obliteration to include non‐suppurative chronic infections and possibly immunosuppression. Obliteration of lumina in proximal and distal airways was visualized on bronchoscopy, the latter by the use of the ultrathin bronchoscopes. An attempt at invasive intervention by transbronchial breaching of the obstruction was unsuccessful in three cases, and in one case, the obliterative process resolved spontaneously and without any radiologic trace, presumably by resorption or rupture or through development of collateral ventilation. This series highlights the use of bronchoscopy for diagnosis and occasionally for therapeutic intervention in hitherto little recognized obliterative airway lesions. These acquired obliterative lesions should be considered in the evaluation of patients with isolated non‐resolving pulmonary infiltrates or other conditions in which bronchial and bronchiolar patency may be impaired. Pediatr Pulmonol. 2014; 49:E27–E34. © 2013 Wiley Periodicals, Inc.